Inter-relation between "classic" motor neuron disease and frontotemporal dementia: neuropsychological and single photon emission computed tomography study. Issue 5 (May 1995) - Talbot, P R; Goulding, P J; Lloyd, J J; Snowden, J S; Neary, D; Testa, H J
Abstract : The purpose of this study was to examine the possible association between "classic" motor neuron disease (cMND) and frontotemporal dementia (FTD), using neuropsychological evaluation and single photon emission computed tomography (SPECT). Psychological tests assessing language, perceptuospatial, memory, and "frontal lobe" functions were given to patients with cMND and test scores were compared with those of normal control subjects. 99mTc-HMPAO SPECT was performed on patients with cMND, FTD and motor neuron disease (FTD/MND), FTD alone, and normal control subjects. Regional cerebral blood flow indices (rCBFi) were determined in 36 cortical regions, and differences between grouped rCBFi data were investigated by canonical discriminant analysis. There were significant group differences in the scores of picture sequencing and token tests in patients with cMND compared with normal controls. Regional CBFi data showed frontal and anterior temporal reductions in patients with cMND compared with normal controls. A similar pattern of SPECT abnormality was seen in patients with FTD/MND and FTD alone, but to a more pronounced degree than in patients with cMND. Neuropsychological and SPECT findings in cMND, FTD/MND, and FTD showed a common pattern of cerebral involvement, most pronounced in the second two conditions. It is suggested that cMND, FTD/MND, and FTD represent a clinical range of a pathological continuum.